THE RELATIONSHIP BETWEEN INSULIN USAGE ADHERENCE AND FEMALE SEXUAL DYSFUNCTION IN TYPE 2 DIABETES MELLITUS PATIENTS IN RSUD CUT MEUTIA NORTH ACEH - Debbyousha, Maulina; Zufry, Hendra; Sucipto, Krishna; Sawitri, Harvina; Siregar, Suhaemi; Alfajri, M. Jailani; Siregar, Erwin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION A normal sexual health is an important part of life and relationship, it affects overall quality of life, physical and emotional health. Sexual dysfunction is one of the complications in patients with Type 2 Diabetes Mellitus (T2DM). Female sexual dysfunction is more difficult to diagnose and treat because of the intricacy of female sexual response. Insulin usage adherence is an important issue of T2DM treatment, ineffective insulin therapy contributes to poor glycemic control and places patients at risk of complications. This research was carried out in North Aceh, one of the districts in Aceh that applied Islamic sharia. Female sexual function is an issue that is rarely discussed in North Aceh. METHODOLOGY This study was an observational study with cross-sectional approach. Data were analysed with chi square statistical test, using statistic software and obtained with interview. Female sexual dysfunction was measured by using Female Sexual Function Index (FSFI) -9 items. Insulin usage adherence was measured by using Morinsky Insulin Adherence Scale. RESULTS There were 39.3% respondents who had high adherence, 30.3% respondents had medium adherence, and 30.3% respondents had low adherence. There were 54.5% respondents who had sexual dysfunction and 45.4% didn’t have sexual dysfunction. Statistical paired chi square with α 0.05 indicated that there was association between insulin usage adherence and female sexual dysfunction in T2DM patients (p value = 0.008). CONCLUSION There was a significant relationship between insulin usage adherence and female sexual dysfunction in T2DM patients.